The Bell Curve: Corrected for Skew - Kupermintz, Haggai (Education Policy Analysis Archives, 1996)
This commentary documents serious pitfalls in the statistical analyses and the interpretation of empirical evidence presented in The Bell Curve. Most importantly, the role of education is re-evaluated and it is shown how, by neglecting it, The Bell Curve grossly overstates the case for IQ as a dominant determinant of social success. The commentary calls attention to important features of logistic regression coefficients, discusses sampling and measurement uncertainties of estimates based on observational sample data, and points to substantial limitations in interpreting regression coefficients of correlated variables.